Kemampuan Komunikasi Matematis Siswa melalui Pendekatan PMRI pada Konteks Alat Musik Angklung - Yuliana, Vera; Zulkardi, Zulkardi; Susanti, Ely (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
This research aims to describe students' mathematical communication skills through PMRI approach. This research method used descriptive qualitative by involving 9 students in Palembang city as research subjects. Data collection techniques used tests and interviews with descriptive qualitative data analysis techniques. The results of this research showed that students who scored high in mathematical communication ability could write answers according to the indicators correctly and completely. In students who obtained a medium score, the student solved the problem according to the indicator but less precise and incomplete. While students who obtained a low score, these students have not been able to answer questions based on indicators of mathematical communication skills correctly and there are still many errors in solving the problems given. For future researchers to see students' mathematical communication skills can use other contextual problems. After analyzing the students' answers, the average result of students' answers is 72.23% which is categorized as moderate.